Analysis of breakdown mechanism based on contact area and field enhancement factor of different electrode-material combinations - Akin, Firat; Arikan, Oktay (WILEY, 2022)
In this study, the effect of electrode configurations on breakdown performances of polyethylene terephthalate, presspaper and styrene-butadiene rubber/natural rubber blend is investigated with the considerations of electrode area and field enhancement factor. Cylinder-cylinder, spherical-cylinder and point-cylinder electrode configurations are used for breakdown experiments and the measurements are taken according to the rapid-rise method. Characteristic breakdown voltages of the materials are obtained for each electrode configuration by performing Weibull analysis on experimental results. Based on the characteristic breakdown voltages, the characteristic breakdown strengths of the materials are calculated for each case with a field enhancement factor. According to the experiments and the calculations, it has been determined that the characteristic breakdown strengths of the materials increases as the curvature radius of the high voltage electrode decreases. In addition, it is found that characteristic breakdown voltages are inversely proportional to the electrode areas for polyethylene terephthalate and presspaper, whereas this relationship is different for styrene-butadiene rubber/natural rubber due to the dramatic increase in field enhancement factor of the point-cylinder electrode configuration. Finally, these behaviors are explained by numerical calculations and the simulation studies performed in COMSOL Multiphysics software.
Keywords: breakdown strength; electrode area; field enhancement factor; non-uniform electric field; solid dielectrics; Weibull distribution; DIELECTRIC BARRIER; PARTIAL DISCHARGE; IMPACT; OIL; Energy & Fuels; Nuclear Science & Technology